2013
DOI: 10.3390/ijms140714800
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Targeted Agents as Radiosensitizers in Cancer Therapy—Focus on Prostate Cancer

Abstract: As our understanding of the molecular pathways driving tumorigenesis improves and more druggable targets are identified, we have witnessed a concomitant increase in the development and production of novel molecularly targeted agents. Radiotherapy is commonly used in the treatment of various malignancies with a prominent role in the care of prostate cancer patients, and efforts to improve the therapeutic ratio of radiation by technologic and pharmacologic means have led to important advances in cancer care. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 159 publications
0
28
0
Order By: Relevance
“…However, the potential of FASN inhibitors to radiosensitize tumors has not been evaluated. Radiotherapy is an important element in the clinical management of prostate cancer and its efficacy is expected to be enhanced when combined with radiosensitizing agents (48). We demonstrated that the radiation-induced decrease in the surviving fraction of PC3 clonogens was enhanced when C75 was administered in combination with X irradiation.…”
Section: Figmentioning
confidence: 80%
“…However, the potential of FASN inhibitors to radiosensitize tumors has not been evaluated. Radiotherapy is an important element in the clinical management of prostate cancer and its efficacy is expected to be enhanced when combined with radiosensitizing agents (48). We demonstrated that the radiation-induced decrease in the surviving fraction of PC3 clonogens was enhanced when C75 was administered in combination with X irradiation.…”
Section: Figmentioning
confidence: 80%
“…Moreover, concurrent androgen deprivation is known to have a radiosensitizing effect on the primary. 22,23 Extrapolating this to the nodes, and based on the above data, it is likely that incidental dose of about 36 to 40 Gy received by the obturator region in the present study may be adequate in eradicating microscopic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In radiation therapy, studies in small animal models are a key means to understand and develop treatments for a wide spectrum of diseases (1, 2). Several groups, including ours, have initiated efforts to develop small animal irradiators that mimic human treatment (312).…”
Section: Introductionmentioning
confidence: 99%